Pengaruh Variabel Fundamental Terhadap Harga Saham Perusahaan Terindeks LQ45 Subsektor Perbankan Periode 2018-2022 - Hijjah, Siti Dzul; Alamsyah, Alamsyah (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
The study aims to test and analyze the impact of Return On Assets, Earning Per Share, Debt to Equity Ratio on the Share Price of LQ45 indexed corporations banking subsector period 2018-2022. This research is quantitative and associative. Samples are taken using purposive sampling techniques. In this study the sample amounted to 5 companies out of 9 banking companies listed in the LQ45 index for the period 2018-2022. The data analysis method in this study is panel data regression analysis using Eviews 12. The results of this study show that Return On Assets has a negative and insignificant impact and Earning Per Share has a positive and significant impact on the price of the stock. For further research, it is expected that the researchers will be able to expand the coverage of research objects to other sectors of existing companies listed in the LQ45 index so that they can add more diverse research variables.